Blood parasites of ducks in the British Isles - Worms, M J; Cook, W A (Wildfowl, 1966)
243 birds of 16 species of Anatidae have been examined for blood parasites. Microfilariae were found in Teal, Smew and Pintail and Leucocytozoon in Scaup, Wigeon, Pochard and Teal. Parasites in the Smew, Pochard and Wigeon are considered new host records. Attempts at transmission of the Teal filaria were unsuccessful.